What is the relationship between gestational age and docosahexaenoic acid (DHA) and arachidonic acid (ARA) levels?. (September 2015) - Baack, Michelle L.; Puumala, Susan E.; Messier, Stephen E.; Pritchett, Deborah K.; Harris, William S.
Abstract: Long chain polyunsaturated fatty acids (LCPUFA) including docosahexaenoic acid (DHA) and arachidonic acid (ARA) are increasingly transferred from mother to fetus late in pregnancy. Infants born before this transfer is complete are at risk for deficiency. This study determines the relationship between gestational age (GA) and circulating LCPUFA levels to better understand the unique needs of premature infants born at various GAs. Whole blood was collected within the first 7 days of life from 60 preterm (≤34 weeks GA) and 30 term infants (≥38 weeks GA) and FA levels were analyzed. Since concurrent intravenous lipid emulsion can skew composition data, blood LCPUFA concentrations were also measured. Levels were compared among groups, and linear regression models were used to examine the association between FA composition and GA. Preterm infants had significantly lower DHA and ARA levels than term peers, and whether assessed as concentrations or compositions, both directly correlated with GA ( p <0.0001). Moreover, FA comparisons suggest that premature infants have impaired synthesis of LCPUFAs from precursors and may require preformed DHA and ARA. This study confirms that essential FA status is strongly related to GA, and that those babies born the earliest are at the greatest risk of LCPUFA deficiency.